Focused ion beam ring drilling for residual stress evaluation - Korsunsky, A; Sebastiani, M; Bemporad, E (Elsevier, 2009)
Focused Ion Beam (FIB) milling of ring-shaped trenches (ring drilling) induces controlled gradual strain relief at the surface of residually stressed samples, with the central "island" approaching the unstressed state. Strain change was measured at sample surface via Digital Image Correlation analysis of SEM micrographs of a regular pattern of dots deposited on the sample surface prior to ring drilling. FE modeling of strain evolution with ring drilling depth agrees with experimental observations. The technique proposed represents a substantial improvement over prior attempts, constituting an efficient semi-destructive method for accurate residual stress evaluation at the (sub)micron scale.